Migration and Mitigation of effect from migration (International Journal of Scientific Research and Management (IJSRM), 2019)
The migration of educated professionals, popularly referred to as the Brain Drain, is not new to Sri Lanka. When well educated people abandon their homes of origin towards greener pastures elsewhere, the nation loses enormous amounts of money spent towards their education. It gets no returns from the vast amounts spent on the highly skilled. Along with such brain drain, the less developed lose not only human resources but are forced to either ignore or abandon efforts for development making the economic divide more and more severe. In Sri Lanka, only 10% of new entrants to schools each year, get selected for university education. On completion, most of them migrate for their education elsewhere with improved living conditions and aim towards positions in keeping with their skills. This trend towards migration needs to be arrested and expertise needs to be directed towards national development. This study investigates mitigating brain drain and attempts to reduce the impact of brain drain on a developing country like Sri Lanka. After extensive research with an experimental survey taking into consideration 10 hypotheses and testing with statistical techniques to analyze the data, the study investigates factors leading to brain drain related mostly to Science, Computing, and Engineering related disciplines. It also proposes a sustainable development approach to mitigate the impact of brain-drain on a developing country like Sri Lanka based on a statistical foundation and migrants’ views.